4. Study of Knowledge, Attitude and Action of Buffalo Ranchers in the VillagesAround Nagan Raya Power Plant on the Impact of Fly Ash Exposure - Ira Susanti; Rinidar Rinidar; Sugito Sugito (Universitas Syiah Kuala, 2020)
One of the biggest contributors to air pollution is the production of coal fly-ash from the power plant industry. Fly-ash has an immediate impact on human and animal health around the power plant. Many buffaloes are maintained by Nagan Raya people and are often consumed by the community. The buffalo ranchers in this area release their livestock around the 110 MW Steam Power Plant that using low-rank coal. This ranchers’s behavior raises concerns about buffalo health due to exposure to fly ash. This study aims to examine the relationship between knowledge, attitude, and action of buffalo ranchers to the impact of fly ash exposure on the buffalo they maintain. This research used a cross-sectional design. The research time was done in February 2018 by taking 30 samples as respondents in four villages around Nagan Raya Power Plant. The tools used to assess knowledge, attitudes, and actions were using questionnaires. Data were analyzed statistically with the Chi-Square Test through SPSS for Windows version 17.0. The results showed that there was no significant relationship between the knowledge of buffalo ranchers and the impact of fly-ash exposure (P 0.05) while the attitude and actions of buffalo ranchers had a significant relationship with the impact of fly-ash exposure (P 0.05, P 0 , 05). These results conclude that the buffalo ranchers in the villages around the plant have not understood the impact of fly-ash arising from coal in the Nagan Raya power plant. It is expected that the relevant parties to conduct counseling about the impact of fly-ash exposure and the way of good buffalo management.